Animal babies - Brooke, Susan Rich; Brooke, Michaela Emma (Chicago, USA pi kids, 2014)
Baby animals are cute, and they are even cuter when drawn by the amazing Eric Carle. You and your little one with enjoy reading a rhyming story aloud as they learn new words and press 10 buttons to hear baby animals$1 (Bnames and sounds. This sound book makes the iconic art of Eric Carle come alive!s
Scientific Notions
Keywords: Scientific notions